Berberine-Loaded Carboxylmethyl Chitosan Nanoparticles Ameliorate DSS-Induced Colitis and Remodel Gut Microbiota in Mice - Luqing Zhao; Xueying Du; Jiaxin Tian; Xiuhong Kang; Yuxin Li; Wenlin Dai; Danyan Li; Shengsheng Zhang; Chao Li (Frontiers Media S.A., 2021)
Inflammatory bowel disease (IBD) is a refractory disorder characterized by chronic and recurrent inflammation. The progression and pathogenesis of IBD is closely related to oxidative stress and irregularly high concentrations of reactive oxygen species (ROS). A new oxidation-responsive nano prodrug was constructed from a phenylboronic esters-modified carboxylmethyl chitosan (OC-B) conjugated with berberine (BBR) that degrades selectively in response to ROS. The optimized micelles exhibited well-controlled physiochemical properties and stability in a physiological environment. OC-B-BBR micelles could effectively encapsulate the anti-inflammatory drug berberine and exhibit ideal H2O2-triggered release behavior as confirmed by in vitro drug loading and release studies. The in vivo anti-inflammatory effect and regulation of gut microbiota caused by it were explored in mice with colitis induced by dextran sodium sulfate (DSS). The results showed that OC-B-BBR significantly ameliorated colitis symptoms and colon damage by regulating the expression levels of IL-6 and remodeling gut microbiota. In summary, this study exhibited a novel BBR-loaded Carboxylmethyl Chitosan nano delivery system which may represent a promising approach for improving IBD treatment.